Accidental knotting and subsequent removal of a catheter from the epidural space in an adult cow: a case report. Issue 12 (7th November 2017) - Doodnaught, Graeme M.; Constant, Caroline; Desrochers, André; Pang, Daniel S. J.
Key Clinical Message: This is the first reported case in the veterinary literature of a knot in an epidural catheter. The report reviews this very rare complication and describes options for investigation and retrieval of catheters entrapped in the epidural space of any species. Abstract : This is the first reported case in the veterinary literature of a knot in an epidural catheter. The report reviews this very rare complication and describes options for investigation and retrieval of catheters entrapped in the epidural space of any species.